Estudo morfológico do tecido hepático de Leporinus macrocephalus - Bombonato, Maria Terezinha Siqueira [UNESP]; Rochel, Sabrina Santos [UNESP]; Vicentini, Carlos Alberto [UNESP]; Bastos, Fernando [UNESP] (Universidade Estadual de Maringa, 2007)
The objective of this work was to analyze the liver of Leporinus macrocephalus at the macroscopic and histologic level by evaluating the characteristics of the hepatic tissue. The fishes from a fishery in Bauru, S.P., were collected and sacrificed by destroying the spinal cord; afterwards the collected hepatic tissue was fixed and followed by histological routine. Macroscopic analysis of L. macrocephalus liver showed an organ of homogeneous structure, with red-brown color, located in the medial region of the body, caudal to heart and after the gills. It showed 3 pyramidal lobes, one central and two lateral right and left. The histological analysis showed the hepatic tissue constituted by hepatocytes cords surrounded by sinusoids, named muralium duplex. It yet revealed the diffused, distribution bile system by hepatic parenchyma, showing ducts with simple cubic epithelium, surrounded by muscular fibres and connective tissue. Cells of the exocrine pancreatic tissue were observed surrounding blood vessels in acinar arrangement as zymogen granules. Furthermore, there are melanomacrophages centers distributed along the hepatic parenchyma, preferably next to the blood vessels, constituted by cells accumulating material, such as melanin and lipofucsin, whose presence may be related to the nutritional status of the fish.
Morphological study of the hepatic tissue of Leporinus macrocephalus
Keywords: Leporinus macrocephalus; Liver; Morphology; Teleostei; enzyme precursor; lipofuscin; melanin; animal tissue; connective tissue; controlled study; fish; hepatobiliary system; histology; leporinus macrocephalus; liver; liver parenchyma; muscle cell; nonhuman; nutritional status; pancreas; spinal cord; Pisces